Factors Causing Elementary School Teacher Education Students' Difficulties in Understanding Mathematics Courses (Universitas Pendidikan Indonesia, 2025)
This study investigates the main factors causing difficulties faced by PGSD students in learning mathematics, driven by internal issues like low motivation and anxiety, as well as external factors such as teaching methods and the learning environment. The findings aim to serve as a foundation for improvements in teaching practices, student support, and institutional strategies. This study used a mixed-methods survey design using factor analysis to identify the underlying dimensions of students’ learning difficulties. The population comprised second-semester PGSD students at Ahmad Dahlan University (2024/2025), with 41 survey participants. Instruments included an observation checklist, a structured questionnaire, and a semi-structured interview guide. The collected data were tested for validity using the Kaiser-Meyer-Olkin Measure of Sampling Adequacy and Bartlett's Test of Sphericity. The MSA value was 0.707 in the first stage and 0.751 in the second stage, both exceeding the threshold of 0.50. Bartlett's Test showed a significance level of 0.00, which is smaller than 0.05, indicating that the data is suitable for factor analysis. The results showed that there are four main factors that contribute to students' difficulties in learning mathematics, namely: (1) Learning and Academic Support Factor (eigenvalue 4.858, variance 34.703%), (2) Individual Ability and Attitude Factor (eigenvalue 2.156, variance 15.396%), (3) Family Environment Factor (eigenvalue 1.639, variance 11.710%), and (4) Health Factor (eigenvalue 1.171, variance 8.363%). These findings were supported by interviews with six students, whose experiences aligned with the identified factors, providing a more comprehensive understanding of the challenges they faced in learning mathematics.